Altered plasma levels of βC and γC chain cytokines and post-treatment modulation in tuberculous lymphadenitis. (February 2021) - Kathamuthu, Gokul Raj; Moideen, Kadar; Sridhar, Rathinam; Baskaran, Dhanaraj; Babu, Subash
Graphical abstract: Highlights: TBL individuals exhibit altered βC and γC chain cytokines compared to LTB and HCs. IL-5, IL-2 and IL-4 levels were significantly different in TBL compared LTB and HCs. Anti-tuberculosis treatment significantly modulates γC (IL-2, IL-7) chain cytokines in TBL. Overall, altered systemic levels are the characteristics feature of immune alteration associated with TBL. Abstract: Background: Alterations in β common (βC) and γ common (γC) chain cytokines have been described in pulmonary tuberculosis. However, their role in tuberculous lymphadenitis (TBL) disease has not been assessed. Methods: Thus, in the present study, we have examined the systemic levels of βC and γC chain cytokines in TBL, latent tuberculosis (LTB) and healthy control (HC) individuals. We have examined the discriminatory potential of both family of cytokines using ROC analysis. Finally, we measured the pre and post-treatment responses of these cytokines after anti-tuberculosis treatment. Results: TBL individuals exhibit significantly increased (IL-3) and diminished systemic levels of (IL-5, GM-CSF) βC cytokines compared to LTB and HC individuals. TBL individuals also exhibit significantly diminished (IL-2, IL-7) and elevated (IL-4, IL-9) levels of γC cytokines compared to LTB and/or HC. ROC analysis shows a clear discriminatory capacity of both βC (IL-5) and γC (IL-2) chain cytokines to distinguish TBL from LTB and HCs. The systemic levels of βC chain cytokines were not significantly altered, but in contrast γC (IL-2 and IL-7) cytokines were significantly modulated after treatment. Finally, no significant correlation was observed for βC and γC chain cytokines with their respective lymphocyte count of TBL individuals. Conclusions: Hence, we conclude that altered plasma levels of βC and γC cytokines are the characteristics of immune alteration in TBL disease and certain cytokines were modulated after treatment.